Safe bonds for the European Monetary Union: Strengthening bailout ban with more robust financial system - Philipp Engler; Christoph Große Steffen (DIW Economic Bulletin, 2014)
The cost of state bankruptcy in the euro area is incalculable due to the repercussions for the financial system. As a result of contagion effects, there is a risk that the entire Monetary Union could be pushed into deep recession. This forces euro area member states to implement rescue packages during periods of crisis, at a high costto taxpayers. The bailout policy adopted during the most recent crisis was an indication that sovereign debt in the euro area would be subject to joint liability. This temporarily eliminated incentives for national budgetary discipline. On this basis, it is argued that enhancing the institutional framework of the euro area in the long term by issuing common bonds would alleviate existing distortions of fiscal incentive effects in the euro area. Such a "safe haven" for the euro area could make a major contribution to stabilizing the financial system during periods of crisis. The positive impact this would have on the banking system could reduce the indirect costs of restructuring government debt which, in turn, would make restructuring debt from public debtors in the euro area economically feasible. This would strengthen the no-bailout rule which, again, is likely to result in an increasingly risk-based approach to interest on national debt. With this in mind, limited joint liability under strict conditions would be a welcome measure since it takes advantage of market incentives to cut public spending and consequently helps alleviate the problem of over-indebtedness in the euro area in the long term. As a prerequisite for creating common bonds, binding fiscal rules must be introduced in order that some sovereignty rights can be delegated to a central fiscal authority. In the short term, therefore, the required conditions for common bonds are not in place.
Keywords: E44; F55; H63; 330; monetary union; sovereign debt crisis; banking crisis; fiscal transfers; institutional reform